Validity of instrument to measure primary school mathematics teachers’ acceptance of m-learning applications - Mohamad Ikram Zakaria; Mohd Fadzil Abdul Hanid (International Journal of Evaluation and Research in Education (IJERE), 2023)
Mobile learning (M-learning) is one of the proposed technology-based methods for teaching mathematics in today’s education 4.0 era. This method enables teachers to conduct instruction and learning without being bounded by walls, wires, and the need for specialized physical infrastructure and facilities. This study was conducted to develop and validate an instrument for evaluating primary school mathematics teachers’ acceptance of M-learning applications in problem-solving teaching involving six variables. This research is quantitative and utilizes a questionnaire to collect data. This study involved a total of four experts and 120 participants. Cronbach’s alpha and Exploratory Factor Analysis were used to perform a descriptive analysis of the data. Cronbach’s alpha was determined to be 0.934, with a factor eigenvalue greater than 1. The Kaiser–Meyer–Olkin value for each construct is 0.50, whereas Bartlett’s test value is statistically significant (<0.5). Each item has a factor loading of 0.50 and a variance of ≥60%. The findings showed that this instrument contains six constructs and nineteen appropriate items. It also indicated that this instrument could be used to investigate perceptions of the primary school mathematics teachers’ acceptance of m-learning applications in problem-solving teaching instruments involving performance expectancy, effort expectancy, social influence, facilitating conditions, behavioral intention, and usage behavior (attitude).